2007
DOI: 10.1007/s10764-006-9104-6
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in Diet and Activity Patterns of Macaca tonkeana in Response to Anthropogenic Habitat Alteration

Abstract: I examined how Sulawesi Tonkean macaques (Macaca tonkeana) respond in terms of their diet and activity patterns to anthropogenic habitat alteration in Lore Lindu National Park, Sulawesi, Indonesia. Anthropogenic habitat alteration comprised clearing of forest for agriculture and small-scale forest product collection. I quantified the diet and activity of 2 groups (CH and Anca), occupying habitats with different levels of alteration, via scan sampling. Tree abundance, key food specific density, and fruit produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 42 publications
6
95
0
Order By: Relevance
“…At the time of the study (November 2005-March 2006, the group consisted of ten individuals: one adult male (>5 yr), five adult females (>4 yr) and four juveniles (1-3 yr), which is comparable to the composition of wild groups (Pombo et al, 2004;Riley, 2005Riley, , 2007Supriatna et al, 1992). Wild Tonkean macaques are typically found in the primary and secondary rainforests of Sulawesi (Indonesia) and are mainly frugivorous (Pombo et al, 2004;Supriatna et al, 1992).…”
Section: Subjects and Environmentmentioning
confidence: 92%
See 2 more Smart Citations
“…At the time of the study (November 2005-March 2006, the group consisted of ten individuals: one adult male (>5 yr), five adult females (>4 yr) and four juveniles (1-3 yr), which is comparable to the composition of wild groups (Pombo et al, 2004;Riley, 2005Riley, , 2007Supriatna et al, 1992). Wild Tonkean macaques are typically found in the primary and secondary rainforests of Sulawesi (Indonesia) and are mainly frugivorous (Pombo et al, 2004;Supriatna et al, 1992).…”
Section: Subjects and Environmentmentioning
confidence: 92%
“…Animals are known to selectively use their habitat and change their activity patterns according to the type and strength of ecological pressure in order to maximize their fitness (Boinski and Garber, 2000;Hill, 2006). Apes, for example, choose bed or nesting sites where their preferred food is available (Ancrez et al, 2004;Riley, 2007). Chacma baboons Papio hamadryas ursinus and savannah chimpanzees Pan troglodytes verus are known to use caves on a thermoregulatory basis, including sleeping in caves because they are more comfortable than sleeping outside (Barrett et al, 2003;Pruetz, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of the study (May 2006 to August 2006) it consisted of 22 individuals: two adult males (17 and 8 years old), 11 adult females (16,14,12,11,11,11,8,7,7,7 and 6 years old), two sub-adult females (both 4 years old) and seven infants (<1 year old). The composition of the two groups was comparable to several wild groups (Makwana, 1978;Pombo et al, 2004;Riley, 2007). We did not analyse infant behaviours, as it was not always possible to distinguish these individuals within the group.…”
Section: Subjects and Study Areamentioning
confidence: 99%
“…In this study, the nutrient contents of these five tree species the highest in fibre, as shown in Table 1. In addition, in the study by Hambali et al (2014), M. fascicularis in Kuala Selangor were found to prefer fig fruits as a staple food, and a study by Riley (2007) (MacKinnon et al 1996). In this study, the fig species included F. microcarpa and F. tinctoria ssp.…”
Section: Nutritional Characteristics Of the Diet Of Long-tailed Macaquesmentioning
confidence: 95%